Landscapes and Landforms of Egypt Landforms and Evolution - Embabi, Nabil Sayed (World Geomorphological Landscapes,, 2018)
This book provides a unique reference resource not only for geomorphologists, but for all Earth scientists. It shows how landforms vary enormously across Egypt, from high mountains to endless plains, and presents the vast heritage of forms that have developed under different climates. Richly illustrated with numerous plates and figures, it also includes a bibliography offering exhaustive coverage of the literature.